2019
DOI: 10.18632/aging.102315
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA profiling in the oocyte and cumulus cells reveals that circARMC4 is essential for porcine oocyte maturation

Abstract: Thousands of circular RNAs (circRNAs) have been recently discovered in cumulus cells and oocytes from several species. However, the expression and function of circRNA during porcine oocyte meiotic maturation have been never examined. Here, we separately identified 7,067 and 637 circRNAs in both cumulus cells and oocytes via deep sequencing and bioinformatic analysis. Further analysis revealed that a faction of circRNAs is differentially expressed (DE) in a developmental stage-specific manner. The host genes of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(74 reference statements)
1
21
0
Order By: Relevance
“…Recent work has shown that ARMC4 circular RNAs are crucial to oocyte maturation in pigs. 40 The top MII variant, rs1855111 (in TMEM72-AS1; Figure 4, maternal MII errors locus #1), attained nominal significance in the MI R0, MI younger, and MI older groups, but did not pass the conservative threshold. Although neither TMEM72-AS1 nor the nearby TMEM72 appear to be involved in meiosis, the gene CXCL12 (470 kb downstream) may play a role in ovine oocyte development.…”
Section: Results For Top Associations From Previous Maternal MII Errors Analysismentioning
confidence: 95%
“…Recent work has shown that ARMC4 circular RNAs are crucial to oocyte maturation in pigs. 40 The top MII variant, rs1855111 (in TMEM72-AS1; Figure 4, maternal MII errors locus #1), attained nominal significance in the MI R0, MI younger, and MI older groups, but did not pass the conservative threshold. Although neither TMEM72-AS1 nor the nearby TMEM72 appear to be involved in meiosis, the gene CXCL12 (470 kb downstream) may play a role in ovine oocyte development.…”
Section: Results For Top Associations From Previous Maternal MII Errors Analysismentioning
confidence: 95%
“…What emerges from these studies is surely the maternal contribution in circRNA embryonic inheritance and that circRNAs are actively produced in both oocytes and ovary [263,264]. A genome-wide identification of human ovary circRNAs has been carried out showing circRNA dynamical regulation during ovarian aging, as already suggested for brain [90,263].…”
Section: Circrnas: From Testis To Embryomentioning
confidence: 84%
“…In the ovary, circRNAs have been associated with metabolic processes, serine/threonine metabolism and especially steroid hormone biosynthesis, a critical signaling for normal ovarian functionality. Similarly to the ovary, a circRNA profiling has been examined in both porcine oocyte and cumulus cells revealing 637 and 7067 circRNAs, respectively [264], with potential functions mainly in signal transduction and tight junction regulation, key events in the oocyte-cumulus cell crosstalk.…”
Section: Circrnas: From Testis To Embryomentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, circRNAs have been found to involve in asthma [ 33 , 34 ] and reproductive system tumors [ 35 ], both of which are closely related to the abnormal puberty, and circRNAs are reported to involve in oocyte maturation and hormone synthesis [ 36 ]. For example, Cao et al showed that circRNAs derived from oocytes exhibit with the characteristics of developmental stage-specific expression [ 37 ]. Xin et al revealed that the depletion of circLDLR inhibits the expression of CYP19A1 , thereby reducing the secretion of estrogen in polycystic ovary syndrome [ 38 ].…”
Section: Introductionmentioning
confidence: 99%